2007
DOI: 10.1002/jcp.21041
|View full text |Cite
|
Sign up to set email alerts
|

EGF‐R regulates MMP function in fibroblasts through MAPK and AP‐1 pathways

Abstract: EGF-R regulates cell proliferation, migration, and invasion in fibroblasts. However, the connection of EGF-R with downstream signaling pathways mediating these responses has remained elusive. Here we provide genetic and biochemical evidence that EGF-R- and AP-1-mediated signals are required for MMP expression and collagen contraction in fibroblasts. In EGF-R (-/-) mouse embryonal fibroblasts, basal and inducible expression of several MMPs, including MMP-2, -3, and -14 is impaired in comparison to wild-type cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 63 publications
4
123
0
Order By: Relevance
“…Refer to Table S1 for stromal fibroblasts provide an essential component of the microenvironment for epithelial morphogenesis by promoting EGFR-dependent ECM remodeling via regulation of MMPs and other ECM remodeling enzymes including Lox genes. Our data showing up-regulation of Mmp2, Mmp11, Mmp14, Lox, and Lox3 are consistent with a previous report on regulation of Mmp expression and collagen contraction by EGFR-ERK signaling in mouse embryonic fibroblasts (48). Importantly, several Mmps, including Mmp2, Mmp3, and Mmp14, have been shown to regulate mammary epithelial branching in vivo (49,50).…”
Section: Discussionsupporting
confidence: 92%
“…Refer to Table S1 for stromal fibroblasts provide an essential component of the microenvironment for epithelial morphogenesis by promoting EGFR-dependent ECM remodeling via regulation of MMPs and other ECM remodeling enzymes including Lox genes. Our data showing up-regulation of Mmp2, Mmp11, Mmp14, Lox, and Lox3 are consistent with a previous report on regulation of Mmp expression and collagen contraction by EGFR-ERK signaling in mouse embryonic fibroblasts (48). Importantly, several Mmps, including Mmp2, Mmp3, and Mmp14, have been shown to regulate mammary epithelial branching in vivo (49,50).…”
Section: Discussionsupporting
confidence: 92%
“…MMP-9 activation has been shown to be especially associated with tumor progression and invasion, including mammary tumors (26). In previous reports, inflammatory cytokines, growth factors, or phorbol esters were shown to stimulate MMP-9 by activating different intracellular-signaling pathways in breast cancer cells (27)(28)(29). The inhibitory effect of MMP-9 expression is important for the development of a therapeutic experimental model of tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, we however have found that, when NEP is genetically eliminated, PA SMCs exhibit greater expression of select proliferation-associated biomarkers (PCNA, pERK, c-fos, and c-jun). 59,60 This suggests that NEP depletion promotes a proliferative milieu. In addition, it was found that PA SMCs from NEP Ϫ/Ϫ mice grow much faster than do PA SMCs from NEP ϩ/ϩ mice, which corroborates our observation of enhanced expression of proliferation-associated biomarkers in these cells.…”
Section: Discussionmentioning
confidence: 99%